EUS And s-MRCP Findings In Asymptomatic Subjects with Chronic Pancreatic Hyperenzymemia - Di Leo, Milena; Zuppardo, Raffaella Alessia; Mariani, Alberto; Petrone, Maria Chiara; Cavestro, Giulia Martina; Arcidiacono, Paolo Giorgio; Testoni, Pier Alberto (JOP. Journal of the Pancreas, 2013)
Context A long-standing increase of serum pancreatic enzymes in asymptomatic subjects is considered a benign idiopathic condition called “non-pathological chronic pancreatic hyperenzymemia” (CPH). However, recent studies showed secretin-MRCP (s-MRCP) has brought to light abnormal pancreatic findings in a significant proportion of these subjects. Objective To evaluate pancreatic morphological abnormalities using s-MRCP and EUS in CPH patients. Methods Consecutive patients affected by CPH were investigated with s-MRCP and EUS. EUS findings were compared with consecutive age- and sex-matched controls who underwent EUS investigation for unrelated to pancreaticobiliary disease (CTR). Results Fifty-five CPH subjects and 55 CTR patients were enrolled. Abnormal s-MRCP pancreatic findings were present in 23 CPH cases (41.8%): 10 chronic pancreatitis, according to Cambridge classification; 5 pancreas divisum; 3 pancreatic cyst; 5 Vater’s papilla dysfunction. Pathological EUS pancreatic findings were present in 28 CPH cases (50.9%): 7 pancreatic cystic lesion, 5 pancreas divisum, 1 papillitis, 1 NET, 14 chronic pancreatitis (CP) defined by presence of “consistent with CP” or “suggestive of CP” findings using Rosemont criteria. All cases of CP who undergone s-MRCP had pathological EUS findings suggestive for CP too. Normal EUS findings were more significantly frequent in control patients (n=45) than CPH patient (n=27) (P<0.05). The two groups have same frequencies in detection of cystic lesions, pancreas divisum, papillitis, NET, but chronic pancreatitis was more common in CPH (25.5% vs. 7.3%; P<0.05). Conclusions About half of the patients with asymptomatic chronic pancreatic hyperenzymemia had some pancreatic abnormalities using s-MRCP and EUS. Both these procedures should characterize the diagnostic work-up of these subjects before the hyperenzymemia can be defined with certainly as non-pathological or benign.